Pulmonary Embolism in Patient with Atrial Septal Defect and Deep Vein Thrombotic, The Case Report - Suryantoro M., et al (ACI (Acta Cardiologia Indonesiana), 2017)
Pulmonary Embolism in Patient with Atrial Septal Defect and Deep Vein Thrombotic, The Case Report